ACCELERATION OF IMAGE RECONSTRUCTION PROCESS IN THE ELECTRICAL CAPACITANCE TOMOGRAPHY 3D IN HETEROGENEOUS, MULTI-GPU SYSTEM - Majchrowicz, Michał; Kapusta, Paweł; Jackowska-Strumiłło, Lidia; Sankowski, Dominik (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Electrical capacitance tomography is an innovative method for visualization of industrial processes. One of its main advantages is it’s high time resolution that allows to the usage of ECT in systems with high volatility. In recent years there has been significant development of electrical capacitance tomography 3D, which however, has significantly reduced industrial it’s applications due to the complicated process of image reconstruction. The authors propose the use of multi-node, multi-GPU system to accelerate the process of image reconstruction in ECT 3D.